Urbano Lugrís and the Cultural Movement In Nave Civitas between 2012 and 2018: an Ecocritical Analysis - Acuña, Ana; Rodríguez González, Olivia (Madrygal. Revista de Estudios Gallegos, 2024)
Phase one of an ecocritical and socio-literary research work on the cultural and civic group In Nave Civitas (born in 2012), and its relationship with the literary and plastic work of Urbano Lugrís (1908-1973). The main goals are: research about the origin of this movement and about the election of Urbano Lugrís as an emblem. Sociocultural contextualization of the artist that inspires the group and review of his reception before 2012. Compilation and study of different written and audio-visual documents. Interviews with the members of the group: Xurxo Souto, Ana Badía, Rodrigo Osorio, and Teresa Ramiro. Analysis of the movement’s ramifications through the collaborations and intersections with other groups from Galicia: Malpica, Vilaboa, Vigo, Bueu, etc, having Lugrís as the main axis. After a review of the interviews, the activities and the musical and literary creations of the members, we conclude that there is a series of cultural and vital elements in the trajectory of Urbano Lugrís; and we note that the group uses and recreates these elements, as manifested in the reconstruction of the history of this cultural mainstream in the street, which was born in the city of A Coruña and still develops there. These elements have to do with the rescue of the group’s republican values that impregnate the civic demands of ecological urgency and feminist imprint, with different labour, social and cultural implications in the present. The main activities are the defence of biodiversity and of the values of care and equality, as well as the recovery of public spaces and places of memory, and the use of digital networks, in which the group is very active.
Keywords: Ecocriticism; Sociology of Literature; Feminism; Cultural Activism in Galicia; In Nave Civitas Group; Urbano Lugrís